An Elegant Journey Jewish Teens Encounter Dignity Beyond Death - Berman, Rochel Udovitch (2019)
"The Final Journey: How Judaism Dignifies the Passage" is a trailblazing curriculum developed to teach Jewish death rituals to high school seniors. For the students, it served as a transformative experience. They emerged more reflective, more spiritual, and with a greater sense of the importance of community involvement. The article describes in detail the ten-hour course that features a field trip to a funeral home. Also included are educational challenges, an overview of each session, an in-depth discussion of the impact on students, and a description of the 98-page study guide for teachers.